RUNNING DICTATION TO ACTIVATE STUDENTS IN SPEAKING CLASS - Purnawati, Purnawati (English Education:Journal of English Teaching and Research, 2017)
The aim of the teaching of English as a Foreign Language (EFL), particularly at the Junior High School, is to provide the students with the ability to use the target language for communication. It means that students should be able to perform oral communication in conveying and receiving messages in the language in real and natural world. Consequently, EFL teachers should create a classroom atmosphere where students engage in real-life communication, authentic activities, and meaningful tasks that promote oral language production.This paper offers an interesting and interactive activity as so called Running Dictation to activate students in speaking class. Theoritically, the activity is based on the one of the four strands in speaking class that is Language Focused Learning.The activity may lead students to greater independence and interdependence as it requires each student to perform cooperatively and to interact actively with other students in order to finish a task. Above all,this activity will emerge joyful , interesting and challengingatmosphere in Junior High School class as students feel like playing a game while they are learning and as a result can result in promoting better performance in speaking class. Keywords: running dictation, activate, speaking .